The story of Matthew: an ecological approach to assessment - Chris Walter (Scottish Journal of Residential Child Care)
Although developmental stage theories in psychology have deepened our understanding of looked-after children, they have always run the risk of fixing the individual into a generalised framework so that their uniqueness is obscured (Scourfield, 2002). While theories such as those of Piaget (1959) or Erikson (1963) have forced us to focus on the importance of childhood, it could be argued that they also contribute to a view of the child as completely constrained and determined by internal and external factors (for instance disability, temperament and upbringing).